Build Your Own Mushroom Soil: Microbiota Succession and Nutritional Accumulation in Semi-Synthetic Substratum Drive the Fructification of a Soil-Saprotrophic Morel - Tan, Hao; Yu, Yang; Tang, Jie; Liu, Tianhai; Miao, Renyun; Huang, Zhongqian; Martin, Francis M.; Peng, Weihong (Frontiers in Microbiology, 2021)
Black morel, a widely prized culinary delicacy, was once an uncultivable soil-saprotrophic ascomycete mushroom that can now be cultivated routinely in farmland soils. It acquires carbon nutrients from an aboveground nutritional supplementation, while it remains unknown how the morel mycelium together with associated microbiota in the substratum metabolizes and accumulates specific nutrition to support the fructification. In this study, a semi-synthetic substratum of quartz particles mixed with compost was used as a replacement and mimic of the soil. Two types of composts (C1 and C2) were used, respectively, plus a bare-quartz substratum (NC) as a blank reference. Microbiota succession, substance transformation as well as the activity level of key enzymes were compared between the three types of substrata that produced quite divergent yields of morel fruiting bodies. The C1 substratum, with the highest yield, possessed higher abundances of Actinobacteria and Chloroflexi. In comparison with C2 and NC, the microbiota in C1 could obstruct over-expansion of microorganisms harboring N-fixing genes, such as Cyanobacteria, during the fructification period. Driven by the microbiota, the C1 substratum had advantages in accumulating lipids to supply morel fructification and maintaining appropriate forms of nitrogenous substances. Our findings contribute to an increasingly detailed portrait of microbial ecological mechanisms triggering morel fructification.